Sufistic Education: Contextualization of Moderate-Humanistic Teachings in The Shadziliyah Order, Jombang - Abitolkha, Amir Maliki (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
This study aimed to analyse the Sufi education of the Shadziliyah Order under the wrath of KH Jamaluddin Ahmad Tambak Beras Jombang in the process of forming a moderate humanistic attitude of pilgrims. The research method used is field study with qualitative approach. Data were collected through interviews and observation of non-participants. The results of the study showed that the concept of the teachings of the Syadziliyah order was able to lead pilgrims to have moderate, wise and balanced paradigms. They focus not only on the power of spirituality, but also on social aspects, morality and humanism. Thus, the teaching model of the Shadziliyah Order is based on moderation and integration of science between the Uqrawi and Dunyawi principles as the basis of behaviour in society. In the process of forming the social, moral and spiritual behaviour of the pilgrims of the Shadziliyah Order, it is affirmed not to be inclusive, individualistic and extreme in wading into the Sufi world. The moderate attitude is more emphasised in this order, then the role of the Murysid teachers as educators who are not limited to being spiritual guides, as well as moral and social educators of their congregations. It is also strengthened by Amaliyah, which is consistently practised by the pilgrims who can purify their inner aspects so that it has an impact on their behaviour, attitude and actions.